Inhibitory Activities of Cudrania tricuspidata Leaves on Pancreatic Lipase In Vitro and Lipolysis In Vivo. (10th December 2012) - Kim, Young Sook; Lee, Youngseop; Kim, Junghyun; Sohn, Eunjin; Kim, Chan Sik; Lee, Yun Mi; Jo, Kyuhyung; Shin, Sodam; Song, Yoojin; Kim, Joo Hwan; Kim, Jin Sook
Abstract : To identify effective herb to treat obesity, we screened 115 herbal extracts for inhibition of porcine pancreatic lipase (triacylg-ycerol acylhydrolase, EC 3.1.1.3) activity in vitro . Of the extracts tested, Cudrania tricuspidata leaves exhibited the most pronounced inhibitory effect on lipase activity with an IC 50 value of 9.91 μ g/mL. Antilipid absorption effects of C. tricuspidata leaves were examined in rats after oral administration of lipid emulsions containing 50 or 250 mg C. tricuspidata /kg body weight. Plasma triacylglycerol levels 2 h after the oral administration of emulsions containing C. tricuspidata were significantly reduced compared to the untreated group (P < 0.05 ). These results suggest that C. tricuspidata leaves may be useful for the treatment of obesity.